Using a service blueprint and the service catalogue concept to plan a smart governance system: the case study of the southern Taiwan science park. (27th April 2020) - Lin, Tung-Cheng; Fang, David
To improve the Southern Taiwan Science Park efficiency, the administration of the park used the smart city concept to transform it into a smart science park. Beyond the information and communication technology (ICT), the key to the development of a smart science park was to consider the requirements of the park's relevant stakeholders. Hence, this study applied the concept of persona, a service blueprint, and the service catalogue concept as the planning methodology and used smart governance as an example to demonstrate our planning process. We held focus group meetings with each persona, used a service blueprint to visualise the group's requirements, and utilised a service catalogue to present the service contents of the related smart governance systems. The study suggested that the relevant authority should implement the smart governance data centre, a public equipment management monitoring platform, and a disaster management platform to improve the efficiency and effectiveness of the public service of the park.